Klasifikasi Kinerja Teknisi Pada Pt. Telkom Menggunakan Metode K-Nearest Neighbor - Amidhan, Muhammad; Heriansyah, Rudi; Permatasari, Indah (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
Productivity is expected to support the company's goal of achieving high profits. Technician performance assessment still relies on subjective assessment from the team leader, causing difficulties in objective evaluation. This research aims to improve the appraisal of technician performance at PT Telkom by proposing using the k-nearest Neighbor (k-NN) method as a classification method. The k-NN method was chosen because of its robustness to training data and effectiveness on large training data. The classification process includes finding the distance between two points using the Euclidean equation, sorting the lowest value as the nearest neighbor, calculating the number of neighbors based on the 5 (five) nearest neighbors for the classification of